1927 Mass. Acts 413, An Act Relative to Machine Guns and Other Firearms, ch. 326, §§ 1-2 (amending §§ 121, 123) - (:unkn) unknown (General Publisher, 1927)
Prohibited selling, renting, or leasing a pistol, revolver, or machine gun to a person without a license to possess the same.
--
Keywords: MACHINE GUN RESTRICTION; TRANSFER